Sustained attention on a pre-recorded lecture: an EEG study - Tajidin, Shamsul Omar (2021)
Introduction: Pre-recorded lectures are an essential component of e-learning environments; these lectures should be delivered in a way that promotes learning. Providing pre-recorded lectures across various media channels is beneficial to improve student learning, satisfaction, involvement, and interest. Objective: The primary aim of this study was to evaluate the effect of textbased slide presentation as activity 1 and interactive slide presentation as activity 2 on brain wave oscillation changes that affect attention. Methodology: 30 samples in ASCII format were tested to meet the study objectives. The data were sampled at a rate of 1000hz per second. Data preprocessing removed the effect of AC lines and unwanted frequencies using the HFF, LFF and Notch filters. Different kinds of noise of either extrinsic or artefacts were then removed using DWT and applied over detail coefficients (d) to remove the noise. The DWT decomposed the signal into wavelet coefficients and was reconstructed. A t-test was used to assess whether the means of the two groups were statistically different from each other and to explain the importance of every independent variable in the demand model. Results: The mean of max beta was determined and compared between activity 1 and activity 2. The findings indicated that the P-value was less than 0.05, which meant that both activity 1 and activity 2 affected the pre-recorded lectures when the t value was 5.663 and 7.850, hence the Hₒ was refused by the T-test. Similar findings were obtained for the frontotemporal region, which recorded the highest mean of max beta between 2 activities, and the results also indicated that the P-value was less than 0.05. This implied that both the frontotemporal region in activity 1 and activity 2 affected the pre-recorded lectures when the t value was 6.013 and 6.523, hence the Hₒ was refused by the T-test. Conclusion: Both activities were tested, and statistical analysis results based on the findings indicated that the study failed to accept the null hypothesis. There was enough evidence of notable differences in both learning approaches. In light of this, this study concluded that teaching should be more precise on what elements are required to develop student attention. This, in turn, would help teaching with the right choice of method to meet the requirements.